Morphological, environmental and management factors affecting nutritive value of tall fescue (Lolium arundinaceum) - Insua, Juan Ramón (2018)
The aim of this study was to quantify the relative importance of leaf age and leaf length on the dynamics of neutral detergent fibre (NDF), and 24-h in vitro digestibility of NDF (NDFD) and dry matter (DMD) of tall fescue (Lolium arundinaceum (Schreb) Darbysh.). Mini-swards were conditioned and used to conduct two experiments, the first with 4-cm plant stubble height in spring-summer 2009 and autumn-winter 2011, and the second with 4-cm or 10-cm plant stubble height in spring-summer 2011. Plants were harvested at consecutive leaf-appearance intervals to measure nutritive value up to the four-leaf stage. In parallel, leaf morphogenetic traits (appearance, elongation and lifespan) and sheath length of the successive leaves produced on marked tillers were measured. Leaf NDF contents remained stable with increasing leaf age and length but showed a marked variation across seasons. Leaf NDFD and DMD showed a consistent decrease with increasing leaf age and length, and irrespective of growing season or residual pasture height. The negative effect of leaf age and length on digestibility was related to variations in sheath tube length and associated differences in leaf appearance and elongation rates. These findings highlight the relevance of monitoring the sheath tube length as a complementary measure to leaf stage for further management of the NDFD and DMD of grass forages. Although the focus of this study was tall fescue swards, the same morphogenetic implications on forage nutritive value could apply to other temperate and tropical grass species; however, the testing of this hypothesis warrants carefully controlled investigations.